2017
DOI: 10.1111/nep.12920
|View full text |Cite
|
Sign up to set email alerts
|

“Who matters most?”: Clinician perspectives of influence and recommendation on home dialysis uptake

Abstract: The decisional power around home dialysis in NZ sits with nephrologists. It is therefore critical that nephrologists exercise their decisional power in advocating home dialysis and address reasons why they may not recommend home dialysis to well-suited and appropriate patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 43 publications
(38 reference statements)
0
13
0
Order By: Relevance
“…18,19 In our study, clinicians further reiterated the need for all team members to use remote monitoring, including nephrologists and nephrologists-in-training as a team approach would help further enhance patient-focused care. A team approach is fundamental to patients commencing home dialysis treatments 20 and providing quality of care for patients on PD 21 and training and support for nephrologist and nephrologists-in-training to fully utilise remote monitoring may help to overcome this.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 In our study, clinicians further reiterated the need for all team members to use remote monitoring, including nephrologists and nephrologists-in-training as a team approach would help further enhance patient-focused care. A team approach is fundamental to patients commencing home dialysis treatments 20 and providing quality of care for patients on PD 21 and training and support for nephrologist and nephrologists-in-training to fully utilise remote monitoring may help to overcome this.…”
Section: Discussionmentioning
confidence: 99%
“…21 Additionally, studies of dialysis modality choice suggest that patients place a high value on nephrologists' treatment recommendations. [22][23][24] In contrast, our findings in patients with less advanced CKD suggest that patients who have not yet initiated kidney replacement therapy still rely heavily on their non-nephrologist providers for medical care and CKD treatment and advice. In this study, participants who were in nephrology care longer and who completed more nephrology visits in the previous 2 years were more likely to rely on their nephrologists for medical care.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in the NZ population have identified a lack of confidence, fear of isolation, fear of self‐needling and financial constraints as key barriers to HHD uptake . Additionally, clinician recommendation has a significant impact on decision making around the modality choice, with several recent studies confirming that recommendation from an engaged nephrologist is a prime factor in patients choosing home haemodialysis . Our patient education programme practises a ‘Home First’ approach, emphasising a ‘lifestyle’ rather ‘medical’ match of dialysis modality.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] Additionally, clinician recommendation has a significant impact on decision making around the modality choice, with several recent studies confirming that recommendation from an engaged nephrologist is a prime factor in patients choosing home haemodialysis. 20,21 Our patient education programme practises a 'Home First' approach, emphasising a 'lifestyle' rather 'medical' match of dialysis modality. Pre-dialysis patients attend a multidisciplinary nephrology clinic with nephrologist, nurse educator and dietitian input, and are encouraged to engage in self-care through an individually directed educational programme, using tools that guide the patient to a shared decision based on lifestyle match, irrespective of comorbidity and language barriers.…”
Section: Discussionmentioning
confidence: 99%